2014
DOI: 10.1111/jcpp.12272
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of methylphenidate and atomoxetine on sustained attention in youth with attention‐deficit/hyperactivity disorder

Abstract: Background This study examined the effects of atomoxetine (ATX) and OROS methylphenidate (MPH) on laboratory measures of inhibitory control and attention in youth with attention-deficit/hyperactivity disorder (ADHD). It was hypothesized that performance would be improved by both treatments, but response profiles would differ because the medications work via different mechanisms. Methods 102 youth (77 male; mean age = 10.5 +/− 2.7 years) with ADHD received ATX (1.4 +/− 0.5 mg/kg) and MPH (52.4 +/− 16.6 mg) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 48 publications
9
27
1
Order By: Relevance
“…In addition, the CPT was used for the evaluation of improved pharmaceutical dosage forms of MPH, e.g., extended controlled-release capsules [39]. It was recently demonstrated that atomoxetine (ATX, a nonstimulant selective norepinephrine reuptake inhibitor used for the treatment of ADHD in children and adults) may lead to improved CPT performance, albeit of a smaller magnitude than with MPH [40,41].…”
Section: Neuropsychological Characteristicsmentioning
confidence: 99%
“…In addition, the CPT was used for the evaluation of improved pharmaceutical dosage forms of MPH, e.g., extended controlled-release capsules [39]. It was recently demonstrated that atomoxetine (ATX, a nonstimulant selective norepinephrine reuptake inhibitor used for the treatment of ADHD in children and adults) may lead to improved CPT performance, albeit of a smaller magnitude than with MPH [40,41].…”
Section: Neuropsychological Characteristicsmentioning
confidence: 99%
“…ADHD patients make more false positive errors than healthy adults, and these errors are sensitive to the effects of stimulant treatment in ADHD patients [2225]. Furthermore, performance on this task is sensitive to effects of methylphenidate, an efficacious ADHD treatment [2427]. Stimulant medications such as methylphenidate decrease false positive error rates following three weeks of treatment, with a medium-to-large effect size (η 2 =.21) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, treatment approaches like neurofeedback have been shown to lead to improvements in inhibitory control and to decreases in impulsivity in patients with ADHD [74,75]. From the point of view of medication, it has been suggested that atomoxetine (frequently used as second-line medication) may be more effective in reducing impulsivity than is the case for methylphenidate (first-line treatment), which may in turn be more beneficial in terms of reducing inattention [76,77]. Importantly, only atomoxetine has been shown to increase prefrontal activation during a Stroop task [78].…”
Section: Discussionmentioning
confidence: 99%